Generational changes in multiple sclerosis phenotype in North African immigrants in France: A population-based observational study. - Clotilde Nardin; Clotilde Latarche; Marc Soudant; Camille Dahan; Maud Michaud; Sophie Pittion-Vouyovitch; Francis Guillemin; Marc Debouverie; Guillaume Mathey (PLoS ONE, 2018)
The incidence of multiple sclerosis (MS) changes from generation to generation in ethnically different immigrants compared with native-born people. We aimed to determine whether there are generational changes in MS phenotypes among North African immigrants in France.Cohort study with data from a population-based MS registry to compare the clinical characteristics of 80 first (NAG1) and 167 second (NAG2) generation North Africans with MS living in France with 5200 native-born Europeans. Adjusted Cox models were used to test the association between scores of 3 and 6 on the expanded disability status scale (EDSS) and the "origin/generation" variable.Cox models for EDSS scores 3 and 6 showed a higher risk of score 3 (hazard ratio = 1.738, 95% confidence interval 1.237 to 2.444; P = .002) and 6 (hazard ratio = 2.372, 95% confidence interval 1.626 to 3.462; P<.0001) for NAG1 than Europeans. Being NAG2 was not significantly associated with higher hazards of scores 3 and 6.We found two different phenotypes among NAG1 and NAG2 MS patients in France. NAG1, but not NAG2, have a higher risk of disability than Europeans. This raises the question of environmental factors in MS expression, and advocates appropriate patient management according to generation in immigrants.